Wawasan Kepemimpinan Guru (Teacher Leadership) dan Konsep Guru Penggerak - Mansyur, Abdul Rahim (Education and Learning Journal, 2021)
This paper reviews teacher leadership and the concept of teacher driving. Teachers as leaders in the scope of learning need their own abilities in learning management and in terms of building relationships with other educational ecosystems. Based on the results of this paper, it can be concluded that; First, the leadership of the teachers (teacher leadership) is affecting the ability of learners to achieve the learning objectives and be able to establish communications with other educational ecosystem. The role of teacher leadership is as an interactive, consultative, participatory, and controlling figure. The teacher becomes the central figure in the management and implementation of learning. Efficient teacher leadership can be carried out in a democratic style that makes teachers more open in learning and becomes a collaboration space with students so that they can foster harmonization of intimacy. Second, the concept of the driving teacher is the formulation of educational policies that are directed at producing teachers as learning leaders. The characteristics of the driving teacher are designed as future education patrons who carry out learner-centered learning and empower fellow teachers in their area. Substantially, this policy implements a curriculum that is based on the educational philosophy of Ki Hadjar Dewantara where a learning leader must be able to reflect critically to contextualize these philosophical values in local and national contexts.